An Analysis of the English Textbook “Bright” Used for the Ninth Grade of MTSN 6 Agam - Fadilla, Giani; Amiza, Elsi; Syahrul, Syahrul; Kardena, Absharini (Pusdikra-Publishing.com, 2024)
This research analyzed the English textbook